2011
DOI: 10.1111/j.1600-0684.2011.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper respiratory tract disease in captive orangutans (Pongo sp.): prevalence in 20 European zoos and predisposing factors

Abstract: Results suggest a higher importance of individual factors for the development of URTD than environmental conditions. Bornean, male and hand-reared orangutans and animals related to diseased animals need increased medical surveillance for early detection of respiratory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…a feature passively formed by functional surrounding structures, but its evolutionary retention and inheritance in a given lineage should confer some evolutionary advantages that conquer some known disadvantages this feature has, e.g. risk of sinus inflammation, polypoids, and aplasia and hypoplasia, which produce malformation in the cheek surface and orbital floor (Dumonceaux et al, 1997;Koppe et al, 2006;Zimmermann et al, 2011;. The advantages of such a spandrel-like feature are probably varied for different clades.…”
Section: Discussionmentioning
confidence: 99%
“…a feature passively formed by functional surrounding structures, but its evolutionary retention and inheritance in a given lineage should confer some evolutionary advantages that conquer some known disadvantages this feature has, e.g. risk of sinus inflammation, polypoids, and aplasia and hypoplasia, which produce malformation in the cheek surface and orbital floor (Dumonceaux et al, 1997;Koppe et al, 2006;Zimmermann et al, 2011;. The advantages of such a spandrel-like feature are probably varied for different clades.…”
Section: Discussionmentioning
confidence: 99%
“…3 Other possible predisposing factors may include exposure to human pathogens, overcrowding with fecal contamination of the environment, stressrelated immunosuppression, and altered airway flora related to chronic antibiotic use. 12 In an effort to evaluate the cause and prevalence of chronic respiratory disease in orangutans, a study of medical records of 201 orangutans from 20 European zoos demonstrated a possible genetic association, as diseased animals were related to animals with respiratory disease 93% of the time and healthy animals were related to diseased animals only 54% of the time. 12 The signs of chronic respiratory disease in orangutans are clinically similar to human cases of cystic fibrosis (CF).…”
Section: Brief Communicationmentioning
confidence: 99%
“…12 In an effort to evaluate the cause and prevalence of chronic respiratory disease in orangutans, a study of medical records of 201 orangutans from 20 European zoos demonstrated a possible genetic association, as diseased animals were related to animals with respiratory disease 93% of the time and healthy animals were related to diseased animals only 54% of the time. 12 The signs of chronic respiratory disease in orangutans are clinically similar to human cases of cystic fibrosis (CF). CF is an inherited disease caused by mutations in the cystic fibrosis transmembrane regulator (CFTR) gene.…”
Section: Brief Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…During offspring development, postnatal parental care is imperative. Individuals deprived of breast milk lack certain nutritional elements micronutrients and lipids, which reduce bioactive agents controlling anti-inflammatory and immunological agents, leaving individuals more susceptible to illness and disease, particularly when other aspects of their care are neglected [Goldman, 2002;Lubach and Coe, 2006;Zimmerman et al, 2011]. All of these implications are widely acknowledged, and zoological establishments are encouraging maternal care and natural grouping patterns to reduce unwanted behavioural and developmental consequences, psychological discomfort and stress [Sodaro and Weber, 2000;Wolfensohn and Honess, 2005;Porton and Niebruegge, 2006].…”
Section: Freedom From Fear Distress and Negative Psychological Statementioning
confidence: 99%